Migration and Regional Identity: The Case of Ukrainian Students in the Region of South Bohemia - Gibon, Gaëlle Reine Ingke (Jihočeská univerzita, 2020)
This master thesis on migration and regional identity focuses on the case of Ukrainian student migration in the region of South Bohemia in Czech Republic. It is an exploratory qualitative research. The research question of this study is: How do Ukrainian students perceive the regional identity of South Bohemia and how do they integrate in that region? The objectives behind that question were to see if these migrants perceive a regional identity in that region, if they identify with it and the main challenges they face to integrate.
Migration and Regional Identity: The Case of Ukrainian Students in the Region of South Bohemia
Keywords: Student migration; Ukrainian migration; South Bohemia; national identity; regional identity; integration; Slavic languages; intercultural relations